Techno-Economic Comparison of Different District and Individual Heating and Cooling Systems: Introducing a Simplified Approach applied to a UK Case Study - Marx, Nicolas Oliver; Alton, Verena; Schmidt, Ralf-Roman; Gudmundsson, Oddgeir; Lagoeiro, Henrique; Marques, Catarina; Maidment, Graeme; Maccarini, Alessandro (International Journal of Sustainable Energy Planning and Management, 2026)
Various renewable and infrastructure options are available for decarbonising the heating sector and at the same time cooling is getting increasingly important. Existing approaches and tools for urban heat planning often require detailed modelling and often only address a limited range of heating and cooling (H&C) options. This paper introduces a simplified approach for quick assessment of 4th generation district heating (4GDH), thermal source networks and individual solutions. The approach uses publicly available datasets, a seasonal representation of energy balances and levelised cost indicators under limited early-stage data availability. The approach is validated by comparison with a detailed hourly feasibility study for a large-scale 4GDH case study in the UK. Cost deviations are within pre-feasibility screening ranges (± 30%), while component-level capacities and costs can differ due to deterministic peak sizing and network correlations, which result from the simplified representation of peak loads and network structures. Since these differences are generally acceptable, the proposed approach enables rapid, transparent comparison of H&C systems and thus can support early planning decisions.